The Cambridge companion to the sonnet - Cousins, A. D.; Howarth, Peter; Dubrow, Heather; Henderson, Diana E.; Marotti, Arthur F.; Freiman, Marcelle; Kennedy, William J.; Bates, Catherine; Wilcox, Helen; White, R. S.; O'Neill, Michael; Campbell, Matthew; et al. (Cambridge, UK ; New York : Cambridge University Press, 2011)
"Beginning with the early masters of the sonnet form, Dante and Petrarch, the Companion examines the reinvention of the sonnet across times and cultures, from Europe to America. In doing so, it considers sonnets as diverse as those by William Shakespeare, William Wordsworth, George Herbert and e. e. cummings. The chapters explore how we think of the sonnet as a 'lyric' and what is involved in actually trying to write one. The book includes a lively discussion between three distinguished contemporary poets - Paul Muldoon, Jeff Hilson and Meg Tyler - on the experience of writing a sonnet, and a chapter which traces the sonnet's diffusion across manuscript, print, screen and the internet. A fresh and authoritative overview of this major poetic form, the Companion expertly guides the reader through the sonnet's history and development into the global multimedia phenomenon it is today"--
Introduction / A.D. Cousins and Peter Howarth -- 1. Contemporary poets and the sonnet: a trialogue / Paul Muldoon, Meg Tyler, and Jeff Hilson, edited by Peter Howarth -- 2. The sonnet and the lyric mode / Heather Dubrow -- 3. The sonnet, subjectivity, and gender / Diana E. Henderson -- 4. The English sonnet in manuscript, print and mass media / Arthur F. Marotti and Marcelle Freiman -- 5. European beginnings and transmissions: Dante, Petrarch, and the sonnet sequence / William J. Kennedy -- 6. Desire, discontent, parody: the love sonnet in early modern England / Catherine Bates -- 7. Shakespeare's sonnets / A.D. Cousins -- 8. Sacred desire, forms of belief: the religious sonnet in early modern Britain / Helen Wilcox -- 9. Survival and change: the sonnet from Milton to the Romantics / R.S. White -- 10. The Romantic sonnet / Michael O'Neill -- 11. The Victorian sonnet / Matthew Campbell -- 12. The modern sonnet / Peter Howarth -- 13. The contemporary sonnet / Stephen Burt.
Bibliografija uz radove.
Kazalo
Keywords: Sonnets, English -- History and criticism; Sonnets, American -- History and criticism; Sonnet -- History and criticism; sonet